ENHANCING EFFICIENCY IN DETERMINING QURAN LEARNING GROUPS: A WEBSITE-BASED K-MEANS ALGORITHM APPROACH AT NURUL JADID ISLAMIC BOARDING SCHOOL - Ikhwan Abdillah; Andi Wijaya; Kamil Malik (Jurnal Teknik Informatika (Jutif), 2024)
This research aims to develop a web-based application system using the K-Means algorithm to group students in Quran coaching at the Nurul Jadid Islamic Boarding School in Paiton, Probolinggo. The need for this system is based on the importance of efficiency and accuracy in determining student coaching groups based on their abilities in reading the Quran, including Tajweed, fluency, and memorization scores. This research method involves data analysis from 412 students. The data is processed using the K-Means algorithm to group students into three skill categories: "Good", "Sufficient", and "Poor". The grouping results provide objective and accurate guidance in determining suitable coaching groups for each student. The research results show that the K-Means algorithm is effective in grouping students, thereby improving the efficiency and accuracy of the coaching process. The implementation of web-based technology facilitates access and use of the system by administrators and coaching participants, ensuring that the grouping and coaching processes become faster, more accurate, and more objective. In conclusion, this research successfully develops a more responsive and efficient Quran coaching system, which not only solves specific problems at the Nurul Jadid Islamic Boarding School but also makes a significant contribution to the development of similar systems in other Islamic educational institutions.